2015
DOI: 10.1111/jmp.12183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood pressure in feline night monkeys (Aotus azarae infulatus) under different restraint protocols

Abstract: The results of our study suggest that all restraint protocols tested significantly alter blood pressure in this species of primates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…The HR measurements were close to that described in the literature and, although not significantly, the HR of the females was slightly higher (250 bpm ± 51 SD in males and 267 bpm ± 31 SD in females) 16,18,19 . Although some authors have not described gender differences in HR, 11 the present result may explain the apparent greater sensitivity females are to die suddenly due to restraint stress, as observed empirically by CENP technicians.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The HR measurements were close to that described in the literature and, although not significantly, the HR of the females was slightly higher (250 bpm ± 51 SD in males and 267 bpm ± 31 SD in females) 16,18,19 . Although some authors have not described gender differences in HR, 11 the present result may explain the apparent greater sensitivity females are to die suddenly due to restraint stress, as observed empirically by CENP technicians.…”
Section: Discussionsupporting
confidence: 89%
“…The hypertensive origin of heart diseases in owl monkeys has been discussed by some authors. A survey using ten of CENP's owl monkeys found that animals contained without sedation obtained a systolic blood pressure average around 158 mm Hg 16 . These high measures may be associated with restraint stress; however, constant and invasive monitoring of blood pressure in Aotus nancymae in another research center also obtained values in the range considered hypertensive (>110 mm Hg) while at rest 11 .…”
Section: Discussionmentioning
confidence: 99%
“…There were no variations in systolic, diastolic, and mean blood pressure between the doses nor over time post Telazol ® administration ( Table S1 ). The lack of clinically significant cardiac changes correlates with previous Telazol ® evaluations in capuchins [ 11 ] and owl monkeys [ 13 ]. The respiratory rate decreased over time for all doses ( Table S1 ).…”
Section: Discussionsupporting
confidence: 76%
“…Their combination provides significant muscle relaxation [ 2 ]. The safe use of Telazol ® has already been documented in nonhuman primates including capuchin monkeys [ 11 , 12 ], owl monkeys [ 13 ], rhesus macaques [ 14 , 15 , 16 ], cynomolgus macaques [ 17 ], baboons [ 14 ], chimpanzees [ 18 , 19 , 20 ], and southern brown howler monkeys [ 21 ]. There are a few reports of Telazol ® administration to marmosets, showing a wide dose range [ 9 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple drugs have been studied in primates demonstrating their effects on the cardiovascular system [ 47 49 ]. For example, in small primates, it was demonstrated that multiple anesthetic protocols resulted in increased blood pressure and heart rate, and the isoflurane protocol showed lower value of blood pressure compared to all other protocols [ 50 ]. Using only isoflurane allows to be closer to physiological circumstances and has been indicated for debilitated animals and prolonged procedures in squirrel monkey [ 2 ].…”
Section: Discussionmentioning
confidence: 99%